The social identity of the ATI in Boracay ATI Tribal Organization. - Dilla, Cristo Graciani C.
Little have been known about the Indigenous Peoples of the Philippines, especially with the Ati groups. Even more so, little focus have been placed on the psychological processes that operate and influence their lives. This study attempts to bridge this gap by investigating the social identity of a specific Ati community in Boracay Island, Malay, Aklan. Specfically, this undergraduate research dissected the general themes of their social identity and examines the relationship of the degree of social identification with the BATO and social comparisons with the relevant out-group, the itinerant Atis. Thirty (30) Atis from 39 households in the Boracay Ati Tribal Organization (BATO) participated in this study. Using descriptive correlational research design, the researchers first interviewed the respondents so that emerging themes that describe their social identity are uncovered through content analysis. Second, the degree of their social identification was correlated with the positivity level of their social comparisons using Chi-square goodness of fit test. Results revealed that the social identity of the Atis of BATO is characterized largely by strong and positive relationship with the in-group, structured organizational hierarchy with exclusive membership, and socio-economic gains and opportunities acquire from becoming a member of BATO. Moreover, they are characterized by the tendency to see themselves differently from itinerant Atis and be biased against them. However, results revealed that there is no significant relationship between social comparisons and their degree of identification. The research concluded that the BATO as a community is very much important to its Ati inhabitants so much so that it became a source of opportunities, empowerment, awareness of their ethnicity and positive self-concept.